Biomarkers of Cell Damage Induced by Oxidative Stress in Parkinson's Disease and Related Models - Cesar Tobon-Velasco, Julio; Carmona-Aparicio, Liliana; F. Ali, Syed; Santamaria, Abel (Central Nervous System Agents in Medicinal Chemistry, 2010)
One of the common features occurring in several experimental models of neurodegenerative disorders is oxidative/ nitrosative stress (OS/NS). This event induces a series of deleterious actions involving the primary formation of reactive oxygen and nitrogen species (ROS/RNS), affecting both the structure and function of different biological molecules, and leading to specific toxic processes that compromise cell redox status. Biomarkers are important indicators of normal and abnormal biological processes. Specific biochemical and genetic changes observed in different pathologies bring us comprehensive information regarding the nature of any particular disorder. Parkinson's disease (PD) is a chronic neurodegenerative disorder difficult to study, given the intricate events occurring in the pathology, and also because the resultant clinical phenotype fluctuates over time. At present, we have no definitive diagnostic test, and thus for clinicians there is still expectation that biomarkers will eventually help to diagnose symptomatic and presymptomatic disease, or provide surrogated end-points to demonstrate clinical efficacy of new treatments and neuroprotective therapies. In this review we explore current information on some potential biomarkers of OS/NS in PD models, with special emphasis on the mostrecent findings on this topic.
Keywords: nitrogen oxide